Adhesion of Streptococcus Mutans to Glass Ionomer, BisCem Cement and Enamel: An In Vitro Study - Ezzatollah Jalalian; Ghazal Mofrad; Sogol Ahmadpour (Tehran University of Medical Sciences, 2016)
Objectives: Considering the adhesion of some microorganisms such as Streptococcus mutans (S. mutans) to restorative materials and the unrecognized consequences of this phenomenon, and due to the controversies in this regard, it is important to discover the materials to which the lowest adhesion of S. mutans occurs. The objective of this study was to assess the level of adhesion of S. mutans to glass ionomer (GI), BisCem Cement and enamel. Materials and Methods:In this in vitro experimental study, 12 specimens including five GI blocks (GC America Inc., Alsip, IL, USA), five BisCem blocks (Bisco Inc., Schaumburg, IL, USA) and two enamel blocks were exposed to a bacterial suspension (1×106 mg/mL). After incubation for one hour at 37˚C, the swab samples were taken and cultured in blood agar. The S. mutans colonies were counted by unaided vision after 48 hours of incubation. The results were analyzed using ANOVA followed by the Tukey's test. Results:The number of colonies attributed to enamel, GI, and BisCem blocks was 24±2, 24.2±2.7 and 14.8±1.7 colonies/mm2, respectively. There was no difference between enamel and GI in terms of adhesion of S. mutans (P=0.08 and P>0.001, respectively); however, the difference between these two and BisCem was statistically significant (P= 0.00075 and P<0.001, respectively). Conclusion:Within the limitations of this study, BisCem cement is superior to GI for the cementation of indirect restorations.   Objectives: Considering the adhesion of some microorganisms such as Streptococcus mutans (S. mutans) to restorative materials and the unrecognized consequences of this phenomenon, and due to the controversies in this regard, it is important to discover the materials to which the lowest adhesion of S. mutans occurs. The objective of this study was to assess the level of adhesion of S. mutans to glass ionomer (GI), BisCem Cement and enamel. Materials and Methods:In this in vitro experimental study, 12 specimens including five GI blocks (GC America Inc., Alsip, IL, USA), five BisCem blocks (Bisco Inc., Schaumburg, IL, USA) and two enamel blocks were exposed to a bacterial suspension (1×106 mg/mL). After incubation for one hour at 37˚C, the swab samples were taken and cultured in blood agar. The S. mutans colonies were counted by unaided vision after 48 hours of incubation. The results were analyzed using ANOVA followed by the Tukey's test. Results:The number of colonies attributed to enamel, GI, and BisCem blocks was 24±2, 24.2±2.7 and 14.8±1.7 colonies/mm2, respectively. There was no difference between enamel and GI in terms of adhesion of S. mutans (P=0.08 and P>0.001, respectively); however, the difference between these two and BisCem was statistically significant (P= 0.00075 and P<0.001, respectively). Conclusion:Within the limitations of this study, BisCem cement is superior to GI for the cementation of indirect restorations. Keywords: Bacterial Adhesion; Streptococcus mutans; Glass Ionomer Cements; BisCem cement